Herpes simplex virus mutants defective in the virion-associated shutoff of host polypeptide synthesis and exhibiting abnormal synthesis of alpha (immediate early) viral polypeptides. - Read, G S (1983)
Six mutants isolated from herpes simplex virus type 1 were judged to be defective with respect to the virion-associated function acting to rapidly shut off host polypeptide synthesis in herpes simplex virus-infected cells. The mutants were capable of proper entry into the cells, but, unlike the parent wild-type virus, they failed to shut off host polypeptide syntehsis in the presence of actinomycin D. They were consequently designated as virion-associated host shutoff (vhs) mutants. In the presence of actinomycin D, three of the mutants, vhs1, -2, and -3, failed to shut off the host at both 34 and 39 degrees C, whereas vhs4, -5, and -6 exhibited a temperature-dependent vhs phenotype. Since the mutants were capable of growth at 34 degrees C, it appeared that the vhs function was not essential for virus replication in cultured cells. Temperature-shift experiments performed with the vhs4 mutant showed that an active vhs function was required throughout the shutoff process and that, once established, the translational shutoff could not be reversed. In the absence of actinomycin D, the mutants induced a generalized, secondary shutoff of host translation, which required the synthesis of beta (early) or gamma (late) viral polypeptide(s). The vhs mutants appeared to be defective also with respect to post-transcriptional shutoff of alpha (immediate early) viral gene expression, since (i) cells infected with mutant viruses overproduced alpha viral polypeptides, (ii) there was an increased functional stability of alpha mRNA in the vhs1 mutant virus-infected cells, and (iii) superinfection of vhs1-infected cells with wild-type virus, in the presence of actinomycin D, resulted in a more pronounced shutoff of alpha polypeptide synthesis from preformed alpha mRNA than equivalent superinfection with vhs1 virus. The data suggest that the synthesis of alpha polypeptides in wild-type virus infections is subject to a negative post-transcriptional control involving viral gene product(s) present in infected cell lysates constituting virus stocks. The vhs1 mutant and possibly other vhs mutants contain a mutation in the gene encoding this function.